One, two, buckle my shoe : a Hercule Poirot mystery - Christie, Agatha, 1890-1976 (Christie, Agatha, 1890-1976. Hercule Poirot mysteries., 2011)
"Even the great detective Hercule Poirot harbored a deep and abiding fear of the dentist, so it was with some trepidation that he arrived at the celebrated Dr. Morley's surgery for a dental examination. But what neither of them knew was that only hours later Poirot would be back to examine the dentist, found dead in his own surgery. Turning to the other patients for answers, Poirot finds other, darker, questions."--Back cover.